Entangled stakeholder roles and perceptions of sustainable consumption: An evaluation of sustainable consumption practices in Tianjin, China. (1st October 2018) - Xu, Shengguo; Chu, Chunli; Zhang, Yinan; Ye, Di; Wang, Yiran; Ju, Meiting
Abstract: Sustainable consumption and production are considered to be fundamental ways to solve problems with environmental resources that human beings are facing. There is a broad consensus that promoting sustainable consumption requires the joint efforts of different social actors. This paper aims to define the roles of different stakeholders and the relationships between them, and then establish a modeling framework to analyze those relationships between stakeholders, which include members of government, business, consumer, mass media, environmental non-government organizations, education and research institutions, financial markets, etc. The research found that members of government, business, and consumers make up the core stakeholder network. The modeling framework could be used to evaluate sustainable consumption practices and identify deficiencies that would assist in defining better trajectories. This paper describes the evaluation of sustainable consumption practice in Tianjin, China from a stakeholder perspective to show how the modeling framework can function. According to this analysis, the following six actions may promote sustainable consumption practices in areas like Tianjin: 1) the cultivation of a consciousness of sustainable consumption, 2) the exemplary role of government, 3) a series of laws, regulations, and policies, 4) a thorough sustainable consumption action plan, 5) an insistence on sustainable production and consumption by businesses and consumers, and 6) the concerted efforts of various stakeholders. Highlights: The roles of various stakeholders in sustainable consumption were defined. A modeling framework was created to reveal the relationships between stakeholders. Sustainable consumption practices in Tianjin were evaluated using the framework. Suggestions for sustainable consumption were made for Tianjin and other similar areas.